(untitled) (LACCEI, 2024)
The research sought to ascertain the relationship between digital information, which includes the exchange of digital information, information exchange, information need, and information search, as predictor variables in user satisfaction, and digital inclusion as a mediating variable. The methodology for the study follows a non-experimental research design an electronic questionnaire (n = 30 = 0.959 = 0.959) is administered to a sample of 233 university students from a public university in southern Peru under harsh economic conditions, using reliability and validity tests, factor analysis, and structural equation modeling with partial least squares. The results have shown a statistically significant effect between digital inclusion and satisfaction among university students in extreme poverty, and the levels of satisfaction and user satisfaction maintain a close dependency relationship. The exchange of information positively influences digital inclusion in the same way, that information search maintains a statistically significant relationship.